(untitled) - Russell, Linda (Alexandria, Viginia, 2009)
Ultimate Performance Management: Training to Transform Performance Reviews into Performance Partnerships presents an innovative framework and approach to conducting performance reviews. Through a series of integrated, competency-building half-day and one-day training workshops focused on topics such as coaching relationships, performance goal setting, and diagnosing problems and developing improvement plans, this book has the potential to transform the way your organization approaches performance reviews. Both learning professionals and others can use this book to conduct effective performance review training for all stakeholders in the performance review process including leaders, managers, and even frontline employees who must be engaged in the process to really benefit from it. The book includes complete instructions for the preparation of interactive training workshops along with customizable assessments, training instruments, checklists, planning sheets, exercises, and other tools provided. A companion CD allows users to download more than a 100 pages of support material including ready-to-use PowerPoint™ presentations used to support training sessions and detailed training instructions that allow for quick implementation of training that meets the specific needs of your organization.
Keywords: Performance,Năng suất; Management,Quản trị